Microbial taxa related to natural hydrogen and methane emissions in serpentinite-hosted hyperalkaline springs of New Caledonia - Quéméneur, Marianne; Mei, Nan; Monnin, Christophe; Postec, Anne; Guasco, Sophie; Jeanpert, Julie; Maurizot, Pierre; Pelletier, Bernard; Erauso, Gaël (Frontiers in Microbiology, 2023)
The southeastern part of New Caledonia main island (Grande Terre) is the location of a large ophiolitic formation that hosts several hyperalkaline springs discharging high pH (~11) and warm (<40°C) fluids enriched in methane (CH4) and hydrogen (H2). These waters are produced by the serpentinization of the ultrabasic rock formations. Molecular surveys had previously revealed the prokaryotic diversity of some of these New Caledonian springs, especially from the submarine chimneys of Prony Bay Hydrothermal Field. Here we investigate the microbial community of hyperalkaline waters from on-land springs and their relationships with elevated concentrations of dissolved H2 (21.1–721.3 µmol/L) and CH4 (153.0–376.6 µmol/L). 16S rRNA gene analyses (metabarcoding and qPCR) provided evidence of abundant and diverse prokaryotic communities inhabiting hyperalkaline fluids at all the collected springs. The abundance of prokaryotes was positively correlated to the H2/CH4 ratio. Prokaryotes consisted mainly of bacteria that use H2 as an energy source, such as microaerophilic Hydrogenophaga/Serpentinimonas (detected in all sources on land) or anaerobic sulfate-reducing Desulfonatronum, which were exclusively found in the most reducing (Eh ref H2 ~ −700 mV) and the most H2-enriched waters discharging at the intertidal spring of the Bain des Japonais. The relative abundance of a specific group of uncultured Methanosarcinales that thrive in serpentinization-driven ecosystems emitting H2, considered potential H2-consuming methanogens, was positively correlated with CH4 concentrations, and negatively correlated to the relative abundance of methylotrophic Gammaproteobacteria. Firmicutes were also numerous in hyperalkaline waters, and their relative abundance (e.g., Gracilibacter or Dethiobacter) was proportional to the dissolved H2 concentrations, but their role in the H2 budget remains to be assessed. The prokaryotic communities thriving in New Caledonia hyperalkaline waters are similar to those found in other serpentinite-hosted high-pH waters worldwide, such as Lost City (North Atlantic) and The Cedars (California).